Synergistic Effects of Interferon-γ and Vitamin D3 Signaling in Induction of ILT-3highPDL-1high Tolerogenic Dendritic Cells - Švajger, Urban; Rožman, Primož J. (Frontiers in Immunology, 2019)
In the past, interferon (IFN)-γ and vitamin D3 (vit D3) have both been associated with induction of tolerogenic characteristics in human dendritic cells (DCs). Although there are only a few reports on interdependency of their actions, the interplay between IFN-γ and vit D3 has been clearly demonstrated in certain aspects of immune reactivity. Since both agents have been associated with regulation of immune responses, we set out to examine their functional and mechanistic interactions in context of principal regulators of immunity, the DCs. Combined treatment with vit D3 and IFN-γ caused an extensive expression of immunoglobulin-like transcript (ILT)-3 and programmed death ligand (PDL)-1 on γ/D3DCs, significantly greater than that caused by vit D3 alone. Such γ/D3DCs retained all general DC characteristics. After CD40 ligand-induced activation, they produced increased amounts of IL-10 with almost absent production of IL-12p70. On the other hand, the co-stimulatory potential of γ/D3DCs was weak, with cells possessing the capacity to inhibit CD4+ T cell, CD8+ T cell, as well as memory T cell responses. Naive CD4+ T cells stimulated with γ/D3DCs produced increased amounts of IL-10 with concomitantly low IFN-γ production, upon T cell receptor activation. Additionally, γ/D3DCs completely inhibited granzyme B expression by CD8+ T cells. The percentage of FoxP3-positive cells in co-cultures with naive CD4+ T cells was significantly higher where γ/D3DCs were used as stimulators compared to DCs treated with vit D3 alone and it could be partially reversed by PDL-1 blockade. Interestingly, γ/D3DCs were inefficient at suppressing mDC-induced CD4+ T cell proliferation, but were twice as effective as D3DCs at suppressing mDC-induced CD8+ T cell proliferation. Blockade of indoleamine-2,3-dioxygenase did not reduce the tolerogenic phenotype induced by IFN-γ and vit D3 treatment. Examination of signaling pathways activation revealed a tendency toward increased ERK and Akt phosphorylation in γ/D3DCs. Inhibition of MEK/ERK and PI3K/mTOR pathways significantly reduced the expression of ILT-3 and PDL-1 on γ/D3DCs. In summary, we present the first evidence for existing synergy between IFN-γ and vit D3 in shaping a unique tolerogenic DC activation state.